Effect of supplementing feed grade L-methionine in plant sourced diet on the performance of broiler chicken - Mahmud, T; Hossain, MA; Uddin, MJ; Jahan, I; Ahmad, MH; Hossain, MM (Bangladesh Journal of Livestock Research, 2021)
The study was conducted to investigate the productivity and profitability of broiler on L-methionine supplemented diet. A total of 160 day-old broiler chicks (Cobb 500) was randomly distributed to four dietary supplements, D0 (Control), D1 (0.30 % L-Met), D2 (0.35 % L- Met) and D3 (0.40 % L- Met). Each treatment was replicated five times with 8 birds per cage. The chicks were reared in the battery cages while they were fed with broiler starter diet (crumble) until Day14 of age. The birds with fed with L-Met supplemented diets starting from Day15 until Day35 of age All the diets were iso-caloric and iso-nitrogenous.. Results revealed that the L-Met supplementations were in favor of higher live weight (LW) and better (p<0.05) feed conversion ratio without affecting the feed intake (FI). The D3 diet resulted higher (p<0.01) LW in the birds than all others on Day35 of age. The livability (%) was unaffected (p>0.05) by the dietary supplements. No significant (p>0.05) difference was observed in the relative weights of visceral organs (small intestine, proventriculus, gizzard, liver and heart) except for the spleen. Relatively increased (p<0.05) spleen weight (%) was observed in the D3 diet. The breast weight (%) was increased marginally (p<0.07) in the D3 group, while the other carcass parts; breast weight, thigh weight, wing weight, shank weight, drumstick weight, neck weight, and abdominal fat content were found to be similar (p>0.05) in the dietary groups. Higher profit (p<0.01) and lower production cost (p<0.05) were observed in the D3 group than that of the others. It can be inferred that 0.40% L-Met supplementation in the broiler diet is better for growth performance and profitability. Bang. J. Livs. Res. Vol. 27 (1&2), 2020: P. 1-14